2019
DOI: 10.1016/j.jiac.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Greater burden of chronic comorbidities and co-medications among people living with HIV versus people without HIV in Japan: A hospital claims database study

Abstract: Objective: This study examined the prevalence of chronic comorbidities and the use of co-medications among people living with HIV (PLWH) on antiretrovirals in Japan, compared with age-matched controls without HIV. Methods: This was an observational, retrospective, cross-sectional study using a hospital claims database of Japanese hospitals with advanced medical capabilities (i.e., advanced treatment hospitals, general hospitals, acute care hospitals). We extracted data for PLWH aged !18 years with a prescripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
2
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 33 publications
4
21
2
5
Order By: Relevance
“…Interestingly, in an observational, retrospective Japanese hospital claims database study, PLWHIV on ART were not only found to have a higher comorbidity burden (lipid disorders, diabetes, psychiatric disorders and hepatitis B/C co-infection) than age-matched controls without HIV, but this burden occurred at an earlier age, supporting similar observations in ageing cohorts in Brazil [21,22]. In a separate study (French Dat'AIDS cohort), with the exception of dyslipidemia, comorbidities were even more frequent in the geriatric (≥ 75 years of age) HIV -positive population compared to the elderly (50-74 years of age) HIV-positive populations with 18.4% vs. 4.3% experiencing 4 or more comorbidities, respectively.…”
Section: What Is the Comorbidity Burden In Plwhiv?supporting
confidence: 62%
See 1 more Smart Citation
“…Interestingly, in an observational, retrospective Japanese hospital claims database study, PLWHIV on ART were not only found to have a higher comorbidity burden (lipid disorders, diabetes, psychiatric disorders and hepatitis B/C co-infection) than age-matched controls without HIV, but this burden occurred at an earlier age, supporting similar observations in ageing cohorts in Brazil [21,22]. In a separate study (French Dat'AIDS cohort), with the exception of dyslipidemia, comorbidities were even more frequent in the geriatric (≥ 75 years of age) HIV -positive population compared to the elderly (50-74 years of age) HIV-positive populations with 18.4% vs. 4.3% experiencing 4 or more comorbidities, respectively.…”
Section: What Is the Comorbidity Burden In Plwhiv?supporting
confidence: 62%
“…Although limited in number, the excess comorbidity burden in PLWHIV vs. appropriately age-matched HIV-negative populations has been reported [18][19][20][21]. For instance, in the Australian Positive & Peers Longevity Evaluation Study (APPLES), HIV-positive gay and bisexual men had significantly greater odds of diabetes (OR = 1.97; 95% CI: 1.04-3.75), thrombosis (OR = 3.08; 95% CI: 1.36-6.98) and neuropathy (OR = 34.6; 95% CI: 8.9-134.5) and non-significantly increased odds for heart-disease (OR = 1.71; 95% CI: 0.94-3.1) vs. a matched HIV-negative population [18].…”
Section: What Is the Comorbidity Burden In Plwhiv?mentioning
confidence: 99%
“…Similar to patients with current AUD, our subgroup analysis of patients with HCV and HIV demonstrated elevated incidence of adverse events regardless of gabapentin exposure, which may reflect baseline risk for these adverse outcomes due to increased rates of medical and psychiatric comorbidities and potential medication interactions (Evon et al, 2018;Ruzicka et al, 2019). In contrast to our findings, one small randomized controlled trial comparing the effect of gabapentin with placebo in HIV-associated sensory neuropathy found that participants receiving gabapentin were more likely to report somnolence (12/15 for gabapentin and 2/11 for placebo; p = 0.006), dizziness (9/15 for gabapentin and 5/11 for placebo; p = 0.305), and gait disturbance (7/15 for gabapentin and 3/11 for placebo; p = 0.357) (Hahn et al, 2004).…”
Section: Discussionmentioning
confidence: 69%
“…With the introduction of highly effective combination antiretroviral therapy (cART), persons infected with HIV now have a life expectancy that is closer to that of the general population, particularly in higher income countries [2,3]. Nevertheless, HIV-infected (HIV+) individuals experience a greater burden of co-morbidities, often at a markedly younger age, including cardiovascular disease, frailty, cognitive decline and liver disease [4][5][6]. Among these chronic health conditions, liver disease is especially prevalent, most notably non-alcoholic fatty liver disease (NAFLD), and is a leading cause of death in HIV + individuals [7,8].…”
Section: Introductionmentioning
confidence: 99%